تقييم جودة أداء الممرضات في عملية إعطاء اللقاح في المراكز الصحية بمدينة اللاذقية - اصبيرة ولاء; الحكيم أمل; أحمد سمر (Latakia University Journal -Medical Sciences Series, 2017)
أجريت هذه الدراسة في جميع المراكز الصحية التي تقدم خدمات اللقاح في مدينة اللاذقيةعلى عيّنة قوامها جميع الممرضات اللواتي يقدمن اللقاح للأطفال في المراكز الصحية وعددهن (27) ممرضة،وجميع الأهالي المرافقين للأطفال المراجعين للمركز الصحي بقصد أخذ اللقاح وعددهم (270) عائلة.وجمعت البيانات في الفترة الزمنية الممتدة من شهر تشرين الأول عام 2013 حتى شهر آذار 2014، وفقاُ لاستمارة خاصة معدة مسبقاً لهذه الدراسة وتتضمن (استمارة لتقييم الممرضة أثناءعملية إعطاء اللقاح،واستبيان لتقييم معلومات الممرضات اللواتي يعطين اللقاح،واستبيان لتقييم رضا الأهل عن أداء الممرضات في إعطاء اللقاحات لأطفالهم).وقد هدفت هذه الدراسة إلى تقييم جودة أداء الممرضات في عملية إعطاء اللقاح في المراكز الصحية بمدينة اللاذقية.من أبرز نتائجها أنمعظم الممرضات كان أداؤهن متوسط الجودة في عملية إعطاء اللقاح، كما بينت الدراسة أن غالبيتهن يمتلكن مستوى معلومات ضعيف حول اللقاحات.رغم ذلك كان الأهل راضين بشدة عن أداء الممرضات في إعطاء اللقاحات. This study was conducted in all health centers that provide vaccine services of Latakia city, on a sample of all the nurses who provide the vaccination for children in health centers , their number (27) nurse, and all the parents of children auditors health center to receive the vaccine their number (270) family. Data collected from October 2013 to March 2014, according to note form to evaluatethe performanceofnursesat administrating vaccines , and aquestionnaire to assess information of nurses, and a questionnaire to assess parents’ satisfaction with the nurses’ performance.This study aimed to assess the quality of nurses’ performance in conducting of vaccination at health centers in Latakiacity.The most important results of this study that the quality of performance for most nurses was average in conducting vaccination. The study also showed that the majority of nurses have a weak level of information about vaccines. but the parents were deeply dissatisfied with nurses’ performance in conducting vaccination.